JARINGAN KOMUNIKASI MASYARAKAT SUMBAWA DALAM MELESTARIKAN SATERA JONTAL SEBAGAI AKSARA ASLI SUMBAWA - Ulfha Lestari; Ofi Hidayat (Ilmu Komunikasi, FISIP Universitas Pasundan, 2023)
The Satera Jontal script can be said to be one of the literary cultures of the Sumbawa people which is still maintained today. one of the causes of the lack of knowledge of Sumbawa people about Satera Jontal is due to the degradation of the Sumbawa language, especially in villages. Many still use Indonesian when speaking so there must be a return to the language first and then Satera Jontal can exist like before. This topic is interesting to study because the existence of the Satera Jontal script is currently also experiencing serious problems because it can be said to be endangered so it is necessary to analyze how the communication network is formed in Sumbawa society in an effort to maintain their local script, namely Satera Jontal. Researchers used a qualitative approach and the type chosen was descriptive qualitative with the basis of communication network analysis research. This research uses snowball sampling technique to determine research subjects and then analyzed using Communication Network Analysis to see what kind of communication network is formed between research subjects in preserving Satera Jontal. Most of the Sumbawa community knows about the local script Satera Jontal, but only a few can read and write it. The survey results indicate that information about Satera Jontal is more often obtained from traditional leaders or community figures who have broader knowledge and experience of Satera Jontal. In addition, the community communication network related to Satera Jontal forms a large clique and a personal network model that has an interlocking personal network, which has centralized information exchanged and only spread to a few people within the network. Data analysis indicates that within the formed communication network, each subject plays a different role. Some serve as Hubs (central information sources), Components (part of the network), Bridges (connecting different groups), while others form Cliques (interconnected relationships). The proximity factor, both in terms of family relations and friendships, also influences communication among them.